REINFORCEMENT SKILL DALAM PEMBELAJARAN PAI (Studi Kasus di SMA Bukit Barisan Padang) - Misra, Misra (AT-TALIM, 2012)
The purpose of the study is to describe positive contribution of Reinforcement Skill to make-up of productive behaviour and creativity of student and to investigate supplementary factor and his resistor.Result of research depict that theoretically learn have applied skill reinforcement in course of study but not yet optimal fully, precisely or as according to what expected. Special at study of PAI applying of skill reinforcement enough give positive contribution to creativity and improvement of productive behaviour of student, this matter see step by step can awaken ardour and spirit of learning active student, inovatif, effective, pleasant and creative.Â